Does status quo interpretation affect welfare estimates? - Bakti Hasan-Basri; Shamsul Bahrain Rawi; Hamimi Omar (Penerbit Universiti Kebangsaan Malaysia, 2018)
In choice experiments (CEs), respondents select their most preferred alternative from a series of choices. One of these alternatives is the status quo (SQ) option, which resembles the current scenario. Previous studies have shown that the way the researcher defines the SQ may be different from how the respondents interpret the same option. Using the case study of white water rafting (WWR) recreation, we investigated the effect of SQ definition on the demand function used to estimate the willingness to pay (WTP) of students who participate in WWR. We applied the confidence interval approach, where WTP values are considered to be significantly different if their confidence intervals do not overlap. We found that the WTP estimates for some attributes (i.e., challenge at the advanced and intermediate levels, and advanced safety) were statistically different. The number of significant estimates suggest that the SQ interpreted by the respondents (as an individual and as a group) are better than that of defined by the researchers. Therefore, we suggest that for purchasing decisions related to nature-based recreational goods such as WWR, the SQ should be determined by the respondents rather than by the researchers.